Brown boy singing - Haylen, Leslie (Sydney [N.S.W.] : Angus and Robertson, 1940)
Fictional account of relations betwen European settlers and Aboriginal people in rural New South Wales in the mid nineteenth century.
Keywords: Race relations - Representation - Literature; Literature and stories - Non indigenous - Fiction; Settlement and contacts - Settlers; New South Wales (NSW)